1998
DOI: 10.1021/la980929l
|View full text |Cite
|
Sign up to set email alerts
|

The Shape Transition of Gold Nanorods

Abstract: We report a revised synthetic procedure based on an electrochemical method for preparing an aqueous solution containing suspended Au nanorods. The mean aspect ratios of the Au nanorods can be experimentally adjusted between 1 and 7. The evolution of the longitudinal surface plasmon bands shows an eminently sensitive dependence on the aspect ratios of the nanorods. Their dependence is accordingly described by classical-electrostatic-model predictions. The shape transition of the nanorod particles has been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
426
1
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(460 citation statements)
references
References 23 publications
17
426
1
5
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Time-resolved transient absorption spectroscopy allows one to follow the electronphonon relaxation dynamics in thin metal films [21][22][23][24] and small metal particles. [1][2][3][4][5][6][7][8][9][10][11][12][13] In particular, silver 1,2,9 and gold [2][3][4][5][6][7][8][10][11][12][13] nanoparticles have been studied intensively as they show a strong absorption band in the visible region, which is due to the excitation of the surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Time-resolved transient absorption spectroscopy allows one to follow the electronphonon relaxation dynamics in thin metal films [21][22][23][24] and small metal particles. [1][2][3][4][5][6][7][8][9][10][11][12][13] In particular, silver 1,2,9 and gold [2][3][4][5][6][7][8][10][11][12][13] nanoparticles have been studied intensively as they show a strong absorption band in the visible region, which is due to the excitation of the surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the pump power is increased significantly, the temperature of the metal nanoparticle lattice can be raised to values well above its melting temperature within a few picoseconds (when using ultrashort laser pulses) while the temperature of the environment initially remains constant. This can then lead to size [14][15][16][17] and shape [18][19][20] changes of the nanoparticles before the deposited laser energy can be released to the surrounding medium by phonon-phonon interactions which are usually on the order of 100 ps. 4,7 It was recently reported 29 that gold nanorods prepared by an electrochemical method 30 and encapsulated in micelles in aqueous solution undergo a rod-to-sphere shape transformation within about 30 ps due to melting of the nanorods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work studying the effect of pulsed laser on nanoparticles showed that exposure to irradiation resulted in fragmentation of particles and the generation of new extinction peaks associated with the new population [161,169,[171][172][173]. In this work, particles with diameters ranging from 20 to 50 nm with SPRs ranging from 550 to 750 nm were subjected to NIR pulsed light for 10 min at two different powers (350 and 700 J) [170].…”
Section: The Influence Of Laser Mode and Powermentioning
confidence: 98%
“…Second, most metals crystallize in highly symmetric cubic lattices. Therefore, soft and rigid templates had been used to achieve rod-shaped metal nanostructures, so the seeded method [2,3] and sonoelectrochemical [6,7] is often used.…”
Section: Introductionmentioning
confidence: 99%